The Definition of Failure in Hip Arthroscopy May Include Factors Outside of Reoperation: A Systematic Review - Christopher D. Bernard, M.D; Eva Bowles, M.D; Marcus Trotter, M.D; Levi Aldag, M.D; Erik Henkelman, M.D; Rachel Long, B.S; Paul Schroeppel, M.D; Scott Mullen, M.D; Jacob White, M.L.S; Armin Tarakemeh, B.A; Bryan Vopat, M.D (Elsevier, 2024)
Purpose: To perform a systematic review about the varying definitions of "failure" of hip arthroscopy (HA) in the current literature and to provide a recommendation for the standardization of defining failure of HA. Methods: A systematic search of electronic databases was conducted to identity Level I-IV clinical studies on HA failure published between January 2016 and July 2021 according to Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Inclusion criteria consisted of studies of patients who underwent an arthroscopic hip procedure and included a definition of failure. Studies with patients who underwent open hip procedures and non-full-text articles were excluded. Results: Of 1,290 titles, 85 (6.6%) met inclusion criteria and were analyzed in this review. The most common definition of HA failure used was the need for any subsequent ipsilateral hip surgery (80/85, 94.1%). Among studies that noted reoperation as a cause for failure, conversion to total hip arthroplasty was most frequently cited (66/85, 77.6%) followed by any other reoperation on the ipsilateral hip, including repeat HA, hip resurfacing, and hip periacetabular osteotomy (65/85, 76.5%). Multiple studies used subjective patient-reported outcomes, with use of the modified Harris Hip Score being the most common (17/85, 20%). Conclusions: There are numerous definitions of the term "failure" of HA used by authors in the peer-reviewed literature. A standardized definition of HA failure should be multifactorial. It may include any unplanned subsequent procedures; patient-reported outcomes with emphasis on minimal clinically important difference, substantial clinical benefit, and/or patient acceptable symptom state values; and the inability to return to normal function or sports. Level of Evidence: Level IV, systematic review of Level III and IV studies.